การศึกษาการเกิดฟาวลิ่งและผลกระทบต่อสมรรถนะทางความร้อนของข่ายงานเครื่องแลกเปลี่ยนความร้อนในการอุ่นน้ำม้นดิบ - วราภรณ์ ศรีสุขเจริญปัญญา (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Heat exchangers are widely used in the oil refining industry to preheat crude oil to the temperature suitable for the refining process. After operating the heat exchanger for a certain period of time, fouling will start to accumulate on its surface. As a result, the efficiency of heat transfer in cold tube and hot tube decreases substantially. This research is conducted to study fouling formation and the effect on the thermal performance of 19 heat exchangers network by using linear fouling model, power-law fouling model, falling-rate fouling model and asymptotic fouling model in order to compare the result with that of actual fouling which occurs in the process. The results obtained shows that 42 percent of heat exchanger network obey the falling-rate fouling model. Additionally, this research has developed the fouling model that illustrates the effect of fouling on the thermal performance which causes the loss of heat used to increase the temperature of crude oil before entering the subsequent main process. The finding indicates that heat exchanger which causes network to lose the heat at the maximum level when the fouling increases are heat exchanger E3 and E2. The loss of heat is 9.30 x 10⁷ kW and 5.48 x 10⁸ kW in 600 consecutive days.